Array of nanosheets render ultrafast and high-capacity Na-ion storage by tunable pseudocapacitance - Dongliang Chao (Nature Portfolio, 2016)
Sodium ion batteries are a promising alternative to lithium ion technology, however their sluggish sodiation kinetics currently hinder performance. Here the authors fabricate ultrathin layered tin(II) sulfide nanostructures displaying a pseudocapacitance contribution for high capacity sodium ion anodes.